MAGNETIC RECORD OF LAKE BAIKAL SEDIMENTS: CHRONOLOGICAL AND PALEOCLIMATIC IMPLICATION FOR THE LAST 6.7 MYR - Kravchinsky V.A.; Evans M.E.; Krainov M.A.; Kuzmin M.I.; Peck J.A.; King J.W.; Sakai H.; Kawai T.; Williams D.F. (My University, 2003)
Magnetic remanence vectors for 1472 samples taken from a 601 m core through Lake Baikal sediments are reported along with a complete magnetic susceptibility profile obtained from a pass-through system. Matching the stable remanence directions to the standard geomagnetic polarity time scale (GPTS) provides a robust chronology from the present back to ∼6.7 Ma and yields a remarkably constant sediment accumulation rate of 3.9 cm/kyr. For earlier times – represented by depths >270 m – correlation to the GPTS is more problematic. Susceptibility fluctuations reflect climatic changes that can be matched to the marine oxygen isotope pattern for the last 6.7 Myr. Spectral analysis of the resulting susceptibility time series then indicates that, for the most part, the Milankovitch obliquity signal dominates. However, when the temporal evolution of the frequency content is investigated by analyzing sequences of time windows, a complex picture emerges in which eccentricity and precession power appear during some intervals. Furthermore, there is persistent evidence for significant power in a ‘non-Milankovitch’ band between 28 and 35 kyr.
Keywords: Lake Baikal; magnetic susceptibility; Milankovitch cycles; paleomagnetism; Siberia